Power and faith : politics and religion in Europe from the tenth to the thirteenth century - Huscroft, Richard (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Examining the developments in the political and religious landscape of Western Europe between the tenth and thirteenth centuries, Power and Faith explores the origins of dominant nation Sates and religious institutions in the West emerged out of the fractured and fragmented post-Carolingian world. As a foundational text for those new to the period, the book offers a clear chronological framework for understanding and analysing the emerging polities of Western Europe and an examination of the influence of the Papacy and the Crusades across Christian life and culture. Mixed with careful consideration of major social and economic themes including urbanisation, rural revolution, and the role of women in politics, religion, and society, the book gives a uniquely comprehensive overview of political and religious developments in Western Europe during a neglected yet fundamentally significant period. The book is divided into six parts, part one sets out the scope and aims of the book and discusses the sources used. Parts two and six provide overviews of the political and religious states of affairs in Europe at the start and end of the period respectively. Framed by these sections, the book is divided into three chronologically-ordered parts each containing three chapters, the first offers a brief account of the main historiography of the period concerned, the second provides a thorough account and analysis of the main political developments across Europe during it and the third explores the main religious changes. Power and Faith is an essential introductory guide for students and researchers interested in politics, religion, and society in Western Europe during the middle ages"--
Keywords: Europe -- Politics and government -- 476-1492.; Europe -- Church history -- 600-1500.; HISTORY / Medieval; HISTORY / Europe / General